Transforming the Education Workforce: Learning teams for a learning generation - Education Commission (Education Commission, 2019)
The Education Commission's vision to strengthen, diversify, and transform the education workforce to deliver inclusive, quality education for all.
Keywords: C: International; ___working_potential_duplicate

Universal Basic Education 2018 Indicator Profile for Basic Education Institutions in Nigeria: Public Schools Commission - Universal Basic Education Commission (2019)